2017
DOI: 10.3389/fmicb.2017.01895
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Bacterial Leaf Blight of Rice and Profiling of Secondary Metabolites Produced by Rhizospheric Pseudomonas aeruginosa BRp3

Abstract: Xanthomonas oryzae pv. oryzae (Xoo) is widely prevalent and causes Bacterial Leaf Blight (BLB) in Basmati rice grown in different areas of Pakistan. There is a need to use environmentally safe approaches to overcome the loss of grain yield in rice due to this disease. The present study aimed to develop inocula, based on native antagonistic bacteria for biocontrol of BLB and to increase the yield of Super Basmati rice variety. Out of 512 bacteria isolated from the rice rhizosphere and screened for plant growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(94 citation statements)
references
References 98 publications
1
92
0
1
Order By: Relevance
“…; Yasmin et al . ). In addition, interest in Paenibacillus polymyxa as plant growth promoting rhizobacteria and a potential source of biologically active metabolites, has been increasing (Kim et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Yasmin et al . ). In addition, interest in Paenibacillus polymyxa as plant growth promoting rhizobacteria and a potential source of biologically active metabolites, has been increasing (Kim et al .…”
Section: Introductionmentioning
confidence: 97%
“…Plant growth promoting Pseudomonas and Bacillus spp. have been well developed as efficient biocontrol agents to suppress BLB in rice (Chithrashree et al 2011;Yasmin et al 2017). In addition, interest in Paenibacillus polymyxa as plant growth promoting rhizobacteria and a potential source of biologically active metabolites, has been increasing (Kim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being known as an effective BCA against plant pathogens, it has also been reported as an opportunistic human pathogen (Yasmin et al ). Hence, future clinical trials such as toxicology study on mammals (Yasmin et al ) and haemolytic activity (Radhapriya et al ) should be conducted to ascertain the biosafety of DRB1. Other P. aeruginosa strains such as RRALC3 (Yasmin et al ), PIC25 and PIC105 (Cabanás et al ) were found to be nonhuman pathogenic isolates and they were successfully applied in glasshouse and field settings for the biocontrol of plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Other P. aeruginosa strains such as RRALC3 (Yasmin et al ), PIC25 and PIC105 (Cabanás et al ) were found to be nonhuman pathogenic isolates and they were successfully applied in glasshouse and field settings for the biocontrol of plant pathogens. (Radhapriya et al ; Yasmin et al ; Cabanás et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation